Computer controlled dynamographic system for investigation of complex psychomotoric reaction - Muckus, K.; Danisevicius, J.; Krisciukaitis, A. (Education. Physical training. Sport, 1999)
The reaction of the person to apropriate command consists of latent reaction time and duration of physical movement. It is called a complex psychomotor reaction. Evaluation of physical properties of athletes and/or disabled persons could be done using parameters of psychomotor reaction. Latent reaction time and duration of physical movement are known as independent properties of a person. We tried to reveal the informative parameters about physical abilities of a person using complex investigation of reaction time and physical parameters of movement. The investigations were made using computer analysis of a support reaction force registered during counter movement jumps performed on the force platform. The force platform converts reaction force into electrical signal: voltage of the output signal is proportional to the reaction force. Twelve-bit Analog/Digital converter (CYDAS-1400, Cyber Research Inc. USA) was used to transfer the force platform signal into the computer's memory. Standing jumps were performed at free desired time or as a reaction to the light signals. The switching up of one of 6 lamps situated in a half circle above the investigated person was used as a signal to perform a standing jump. The investigated person touching it during the jump had to switch the lamps out. Controlling software allows preprogramming of up to 20 light signals in test jump series within appropriate time and sequence. The evaluation of dynamic and kinematic parameters of a jump is done using the structural analysis of the reaction force signal. Heuristic methods were used to perform the recognition of elements of reaction force signal during a jump (downward movement, springing, take off, lending). The velocity and track of mass center movement was calculated using consequent integration of the reaction force signal. Up to 20 parameters movement (deepness of squatting, takeoff velocity, maximal reaction force etc.) could be evaluated during such test. The system showed itself as a suitable tool for the testing of either healthy or disabled persons and for selection of the athletes as well. (from: Education. Physical Training. Sport, 1999, 1(30), 51-56, article in Lithuanian)